[Juli Váradi 1]
wedding, nurse & baby, river, waterfall, walking in the forrest, stream, rowing, animals, children playing in the sand, newborn baby & mother, smalling roses, gymnastc, kiel-boat, rowing swimming, skiing, Akropolis, greek village, port, Zoo children playing, gymnastic at morning, health check, at the sea, tennis, little dogs,